Mussel watch program for microplastics in the Mediterranean sea: Identification of biomarkers of exposure using Mytilus galloprovincialis. (September 2022) - Provenza, Francesca; Rampih, Darian; Pignattelli, Sara; Pastorino, Paolo; Barceló, Damià; Prearo, Marino; Specchiulli, Antonietta; Renzi, Monia
Highlights: Biomarkers (BMs) are a useful tool for assessing toxic effects in aquatic organisms. Mytilus galloprovincialis was selected as bioindicator for microplastic exposure. The literature search returned 11 studies, mainly related to oxidative stress BMs. A battery of standardized BMs as well as the inclusion of new ones are needed. Abstract: Microplastics (MPs) are ubiquitous pollutants that have also been detected in the aquatic ecosystems at high concentrations. The use of shellfish as bioindicators is widespread for assessing and monitoring the environmental quality in both freshwater and marine environments. On this path, biomarkers represent an effective tool in monitoring programs. This minireview would broaden the existing knowledge on biomarkers of MPs in the Mediterranean mussel Mytilus galloprovincialis . This species was selected as it is widely distributed across the Mediterranean Sea and used as a bioindicator to monitor the presence of MPs in the marine environment. The literature search returned only 11 studies, mainly related to oxidative stress biomarkers. Although certain biomarkers were explored to estimate the effects of MPs on M. galloprovincialis, a battery of standardized and validated biomarkers as well as the inclusion of new ones are needed in future studies to obtain more comparable and robust findings across the Mediterranean Sea.